2006
DOI: 10.1016/j.jcrs.2006.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Subjective difficulty of each stage of phacoemulsification cataract surgery performed by basic surgical trainees

Abstract: Trainee surgeons found phacoemulsification and capsulorhexis the most difficult stages of cataract surgery early in the learning curve. More time can be dedicated to mastering these steps in the wet lab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 7 publications
6
100
0
1
Order By: Relevance
“…To the best of our knowledge, only one recent literature conducted by Dooley and O'Brien 16 had a comparable study on completion rate of resident-performed phacoemulsification. They measured subjective difficulty of each step of phacoemulsification performed by basic surgical trainees and found that nucleus emulsification and capsulorhexis were the two most difficult steps to These 16 'minor' complications were not severe enough to cause the supervisor to interfere in the surgery (on the contrary, the other 'major' complications were severe or potentially severe that the supervisor took over the rest of the surgery).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one recent literature conducted by Dooley and O'Brien 16 had a comparable study on completion rate of resident-performed phacoemulsification. They measured subjective difficulty of each step of phacoemulsification performed by basic surgical trainees and found that nucleus emulsification and capsulorhexis were the two most difficult steps to These 16 'minor' complications were not severe enough to cause the supervisor to interfere in the surgery (on the contrary, the other 'major' complications were severe or potentially severe that the supervisor took over the rest of the surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Constructing the anterior capsulorhexis manually is technically challenging and recognised as one of the most difficult aspects of cataract surgery to learn. 40 Despite this, it remains unenhanced by advances in technology and is still dependent on freehand, circular tearing by the surgeon. It is estimated that the manual capsulorhexis is complicated by capsular tears in 1% cases 2 and its complexity increases in cases involving shallow anterior chambers, paediatric/mature cataracts, fibrosed capsules, weak zonules or poor visibility.…”
Section: Eyementioning
confidence: 99%
“…In a large multicentre audit, Johnston et al 2 found that the overall PCR rate for 79 junior trainees in their first 2-3 years of training was 5.1%, the particular high-risk period is during the first year of cataract training where the PCR rate may be double this. 7 It is well recognised that a significant learning curve exists for surgeons training to perform cataract surgery. This is the same for experienced surgeons learning the technique for the first time, [8][9][10] or trainees with no previous experience of intraocular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical steps were learnt in order of difficulty. 7 Each step was to be repeated on subsequent cases until the trainer judged it safe to teach the next. The procedure was to be performed under topical anaesthesia unless the patient had a clear preference or there was an indication for a sub-tenons block.…”
Section: Methodsmentioning
confidence: 99%